Career-Specific Parenting Practices and Career Decision-Making Self-Efficacy Among Chinese Adolescents: The Interactive Effects of Parenting Practices and the Mediating Role of Autonomy - Zhang, Yu Chi; Zhou, Nan; Cao, Hongjian; Liang, Yue; Yu, Shulin; Li, Jian; Deng, Linyuan; Sun, Ruixi; Wu, Qinglu; Li, Ping; Xiong, Qing; Nie, Ruihong; et al. (Frontiers in Psychology, 2019)
This study examined the unique and interactive effects of various career-specific parenting practices (i.e., parental career support, interference, and lack of engagement) on Chinese high school students’ career decision-making self-efficacy (CDSE) as well as the mediating role of autonomy in such associations. Based on data from 641 Chinese high school students (47.6% male; mean age = 15.28 years old, SD = .49) in 2016, two moderated mediating effects were identified. Higher level of parental career engagement strengthened the positive association between parental career support and adolescents’ autonomy, which in turn, was associated positively with adolescents’ CDSE. Parental career interference related negatively with adolescents’ CDSE via autonomy when lack of parental career engagement was low, but related positively with adolescents’ CDSE via autonomy when lack of parental career engagement was high. These findings advance our understanding of the underlying processes between career-specific parenting practices and adolescents’ CDSE. Implications for practices were discussed.